2019
DOI: 10.1016/j.heliyon.2019.e02910
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical characterization of cork, phloem and wood from different Quercus suber provenances and trees

Abstract: Sustainability of cork oak (Quercus suber) forests is threatened by biotic and abiotic factors and characterization of potentially differing genetic resources has therefore gained importance. This work addresses the chemical variation of the three tissues of cork oak stems – cork, phloem and wood – in relation to tree and provenance, looking for genetic chemical diversity and for physiological derived differences. The three tissues differ with cork clearly differentiating regarding summative composition, compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The last two are lignocellulosic tissues with moderate content of extractives. Moreover, wood has the highest content of polysaccharides [54]. In our study, we observed a pattern in the distribution of specific bacteria in male mycangia of P. cylindrus, according to the different wood material of the gallery's parts built by the insects (Figure 6).…”
Section: Discussionsupporting
confidence: 49%
“…The last two are lignocellulosic tissues with moderate content of extractives. Moreover, wood has the highest content of polysaccharides [54]. In our study, we observed a pattern in the distribution of specific bacteria in male mycangia of P. cylindrus, according to the different wood material of the gallery's parts built by the insects (Figure 6).…”
Section: Discussionsupporting
confidence: 49%
“…Lignin is an aromatic cross-linked polymer that represents on average 22% of the cork dry mass and is responsible for the structural rigidity of the cells and their resistance to compression [29]. Cork lignin is mostly constituted of G units (guaiacyl units) with an important proportion of H units (hydroxyphenyl units) and minor contents of S units (syringyl units) (H:G:S 1:2.5:0.3, S/G 0.12) [31].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The cellulose and hemicelluloses are less representative and amount up to 16.2% of the cell wall structural components [31]. Hemicelluloses are mainly composed of arabinoxylans with a significant proportion of galactose including uronic acids.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of cork, a homogeneous tissue of phellem cells, depends on the activity of the cork cambium, which covers the trunk and branches of cork oak. Due to the interesting and unique set of physical, biological and chemical properties, such as sealing and insulating features, cork is mainly used for the production of bottle stoppers [ 3 ]. Every year, 80% of worldwide produced cork comes from the Iberian Peninsula, in which Portugal is responsible for almost half of the total global production [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%